Influence of Nitrogen and Weed Management Practices on Productivity of Transplanted Rice (Oryza sativa L.) - Patra, Monalisha; Behura, Akshaya Kumar; Sar, Koushik; Prusty, Anyesha A. (Journal of Tropical Agriculture, 2023)
A field experiment was conducted at the Research Farm, Institute of Agricultural Sciences, SOA, Bhubaneswar during Kharif, 2019. The experiment was laid out in split-plot design with three replications. The treatment comprised of three nitrogen levels (30, 60 and 90 kg ha-1) assigned in the main plot and six weed management practices viz., penoxsulam + cyhalofop butyl @ 125 g ha-1 at 20 DAT fb one hand weeding at 40 DAT, penoxsulam + cyhalofop butyl @ 125 g ha-1 at 20 DAT, bispyribac sodium @ 25 g ha-1 at 20 DAT fb one hand weeding at 40 DAT, bispyribac sodium @ 25 g ha-1 at 20 DAT, two hand weeding at 20 & 40 DAT, weedy check were assigned in the sub plot. The soil of the experimental site was sandy loam in texture with pH value of 5.7. Application of 90 kg N ha-1 recorded highest grain and straw yield and it was at par with application of 60 kg N ha-1. Among the weed management practices two hand weeding recorded the highest grain yield (5.01 t ha-1) followed by penoxsulam+cyhalofop butyl fb one hand weeding (4.81 t ha-1). The nitrogen level of 90 kg N ha-1 along with post-emergence application of penoxsulam+cyhalofop butyl @ 125 g/ha registered highest net return of Rs. 53,976 ha-1 and Rs. 53,569 ha-1, respectively with B:C ratio of 2.23 in each case.